Examining the Relationship of Online Social Networking Sites’ Activities, Customers’ Brand Choice, and Brand Perception in Health-Related Businesses - Nazir, Mehrab; Tian, Jian; Hussain, Iftikhar; Arshad, Adeel; Shad, Muhammad Afzal (Frontiers in Psychology, 2020)
The purpose of this study was to examine the effect of online social networking site activities on brand choice for health-related businesses; the study also explored the mediating impact of brand perception on the connection of online social networking site activities and brand choice in health-related businesses. A self-administered questionnaire was used for data collection from 300 customers, randomly selected from health sector businesses in Pakistan. The findings indicate that online social networking site activities had a substantial influence on customers’ brand choice in health-related businesses and that brand perception mediates the connection between online social networking site activities and customers’ brand choice in health-related businesses. The research also recognized the increasing significance of online social networking sites in health-related businesses. The study offers insights for health-related companies and their managers on visualizing brand perception as well.